Environmental contaminants, heavy metals, and essential elements in Norwegian children and adolescents: Data from the Norwegian environmental biobank - Mari Mohn Paulsen; Nina Iszatt; Amrit Kaur Sakhi; Mahin Karimi; Sharon Lynn Broadwell; Eleni Papadopoulou; Helle Margrete Meltzer; Berit Granum; Anne Lise Brantsæter; Cathrine Thomsen; Line Småstuen Haug (Environment International)
We are daily exposed to various environmental contaminants, including heavy metals, with suspected adverse health effects, and children’s vulnerability is particularly concerning. Human biomonitoring is crucial for measuring these contaminants and essential elements in the body. The Norwegian Environmental Biobank (NEB), coordinated by the Norwegian Institute of Public Health, has collected biological samples (including blood and urine) and questionnaire data systematically since 2016. Identifying population subgroups at elevated risk is essential for implementing protective measures. This study aimed to describe concentrations of environmental contaminants and essential elements in Norwegian children and explored potential clustering among different contaminants. Additionally, we examined differences across groups defined by family socio-demographic factors. A total of 81 environmental contaminants were measured in urine, plasma, and whole blood from children aged 7–14 years participating in NEB. Twenty-six non-persistent and 24 persistent contaminants were quantified in ≥ 50 % of the samples, along with nine essential elements. Most children had contaminant levels below Human Biomonitoring Guidance Values (HBM-GVs). However, nearly all children had bisphenol A levels exceeding the updated tolerable daily intake set by the European Food Safety Authority (EFSA), and 30 % had blood concentrations of the four most common per- and polyfluoroalkyl substances (PFAS) exceeding EFSA’s safe limits. Statistically significant differences in contaminant levels were observed between groups defined by sociodemographic variables such as sex, age, region, and degree of urbanization. Network analysis indicated clear clusters of several contaminants. This study shows that Norwegian children are exposed to a broad range of environmental contaminants, with levels similar to those reported in other studies from Europe and globally.